2021
DOI: 10.3390/ijms22168870
|View full text |Cite
|
Sign up to set email alerts
|

The Gut-Brain Axis in Inflammatory Bowel Disease—Current and Future Perspectives

Abstract: The gut–brain axis is a bidirectional communication system driven by neural, hormonal, metabolic, immunological, and microbial signals. Signaling events from the gut can modulate brain function and recent evidence suggests that the gut–brain axis may play a pivotal role in linking gastrointestinal and neurological diseases. Accordingly, accumulating evidence has suggested a link between inflammatory bowel diseases (IBDs) and neurodegenerative, as well as neuroinflammatory diseases. In this context, clinical, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 164 publications
0
25
0
Order By: Relevance
“…Increasing evidence has shown that the gut-brain axis is pivotal in connecting neurological and gastrointestinal diseases. This communication system, driven by neural, hormonal, immunological, microbial, metabolic, and other signals, is expected to provide a new perspective for explaining the relationship between IBD and neurodegenerative diseases ( 5 ). For example, a cohort study based on the Korean population suggested that patients with IBD had a higher risk of neurodegenerative diseases (Parkinson’s disease [PD] and Alzheimer’s disease [AD]) than non-IBD controls ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing evidence has shown that the gut-brain axis is pivotal in connecting neurological and gastrointestinal diseases. This communication system, driven by neural, hormonal, immunological, microbial, metabolic, and other signals, is expected to provide a new perspective for explaining the relationship between IBD and neurodegenerative diseases ( 5 ). For example, a cohort study based on the Korean population suggested that patients with IBD had a higher risk of neurodegenerative diseases (Parkinson’s disease [PD] and Alzheimer’s disease [AD]) than non-IBD controls ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent molecular findings have also proposed the role of some soluble inflammatory factors from the gut damaged mucosa across the gut–epithelial barrier and the blood–brain barrier as relevant components for both functional and structural changes at the brain level. Namely, it has been widely documented that neuroinflammatory phenomena negatively impact both emotional behavior and cognition ( Crupi et al, 2010 ; Günther et al, 2021 ), thus adding further support to the relationship between CD, neuropsychiatry, and neuroinflammation. This evidence underlines the need for an early diagnosis and full adherence to the GFD to limit, or even prevent, the neuropsychiatric and neurological involvement in CD and its complications ( Hadjivassiliou et al, 2019 ).…”
Section: Discussionmentioning
confidence: 96%
“…Of note, accumulating evidence has suggested that some inflammatory soluble factors derived from the inflamed intestinal mucosa across the gut–epithelial barrier and the blood–brain barrier are major factors for structural and functional alterations in the CNS. In particular, neuroinflammation has been shown to exert detrimental effects on both cognition and emotional behavior [ 72 , 73 ], thus supporting the link between neuroinflammatory, neurological, and psychiatric manifestations in CD. Translationally, these findings highlight the importance of a prompt diagnosis, clinical awareness, and compliance to an adherent GFD to prevent, or at least limit, the neurological and neuropsychiatric involvement in CD and the related disease progression [ 7 ].…”
Section: Discussionmentioning
confidence: 99%